Samantha learns a lesson : a school story - Adler, Susan S., 1946- (American girls collection., 1986)
Samantha is determined to help nine-year-old Nellie, attending school for the first time, with her school work and learns a great deal herself about what it is like to be a poor child and work in a factory.